Comparative Analysis of Fluidized Bed and Plasma Gasifier for Industrial Power Supply System - Thet Aung; Wunna Swe (AI Society & STMIK Indonesia, 2026)
The increasing demand for reliable industrial power generation has driven interest in gasification-based waste-to-energy technologies. This study compares fluidized bed and plasma gasifiers with a focus on electrical power performance. A steady-state energy analysis was conducted to evaluate syngas quality, cold gas efficiency, net electrical output, and overall electrical efficiency under similar operating conditions. Results indicate that fluidized bed gasification achieves higher net electrical efficiency and lower auxiliary power consumption, while plasma gasification provides greater feedstock flexibility. The study supports technology selection for industrial power applications. The power that can be generated from a fluidized bed gasifier and a plasma gasifier has been compared and presented using MATLAB